Tinjauan Yuridis terhadap Keadilan Restoratif dalam Pidana Penyelesaian Perkara di Kepolisian Resort Kota (Polresta) Kupang - Siprianus Damai Nar; Simplexius Asa; Orpa G. Manuain (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
Restorative justice is often understood as a form of approach in resolving a criminal case involving the perpetrator, victim, and other parties such as family, or the community and does not focus on imprisonment, but rather on restoring the victim's condition after the crime has occurred. The Indonesian government has implemented restorative justice in the criminal justice system. Explicitly, restorative justice is stated in Law of the Republic of Indonesia Number 11 of 2012 concerning the Juvenile Criminal Justice System and Regulation of the Republic of Indonesia National Police Number 8 of 2021 concerning Handling of Criminal Acts based on Restorative Justice, recorded in the State Gazette of the Republic of Indonesia in 2021 Number 947. This study aims to determine the model of approach and inhibiting factors in the application of restorative justice in resolving criminal cases. This research is an empirical legal research. The data collection technique was by interviewing informants, and the data analysis used was qualitative analysis. The results of the study show: (1) The restorative justice approach has been implemented at the Kupang City Police by paying attention to values ​​and based on the Pancasila ideology. (2) The implementation of restorative justice in the police is carried out in two models, namely victim offender meeting and Conferencing. (3) the implementation of restorative justice in the police found 3 inhibiting factors, namely legal factors, law enforcement factors themselves and community factors.